Incidence and risk factors of retinopathy of prematurity in Western India – Report from A Regional Institute of Ophthalmology - Vasavada, Dhaivat; Sengupta, Sabyasachi; Prajapati, Vipul K; Patel, Shashank (Nepalese Journal of Ophthalmology, 2018)
Introduction: Retinopathy of prematurity is an important cause of childhood blindness amongst premature babies in developing as well as developed world.Objectives: To report the incidence and risk factors of ROP from a regional institute of Ophthalmology in western India and compare it with the existing scenario.Materials and Methods: This was prospective observational study of babies born at